The effect of cassia fistula emulsion on pediatric functional constipation in comparison with mineral oil: a randomized, clinical trial - Mozaffarpur, Seyyed Ali (BioMed Central, 2012)
BACKGROUND: The prevalence of Pediatric Functional Constipation (FC) has been reported between 0.7% to 29.6%. This study was conducted to compare the laxative effect of cassia fistula emulsion (CFE) with mineral oil (MO) on FC. Cassia fistula is named in Traditional Iranian Medicine (TIM) as “Folus”. MATERIALS AND METHODS: A randomized clinical trial was carried on 81 children (age range: 4–13 years) with FC, according to Rome III criteria in Amirkola Children’s Hospital, Babol, Iran. They received CFE or MO randomly for three weeks. CFE was produced according to the order of TIM references. Children were counted as improved when they exited from Rome III criteria of FC. Frequency of defecation, fecal incontinence, retentive posturing, severity of pain, consistency of stool and anal leakage of oily material were compared between the two groups and with baselines. An intent-to-treat analysis was used. Safety of drugs was assessed with the evaluation of clinical adverse effects. RESULTS: 41 children were assigned randomly to receive CFE and 40 children received MO. After three weeks of medication, 84% of children in CFE group and 50% in MO group (p = 0.002) exited from the criteria of FC, so called improved. All measurable criteria improved in both groups. The frequency of defecation in CFE group improved from 1.7 per week (before the study) to 10.6 per week (at the third week) while this parameter differed in MO group from 2 to 6.1 (p < 0.001). The severity of pain during defecation and consistency of stool improved significantly better in CFE group than MO group (p < 0.05), but there were not any significant differences between the two groups in fecal incontinence and retentive posturing. Anal leakage of oily material occurred as an important complication in MO group while the children in CFE group did not complaint it. Drug’s compliances were not significantly different in the two groups. CFE and MO did not cause clinically significant side effects. CONCLUSIONS: CFE was most effective than MO in the 3-week treatment of children with FC.